Neue Scarabaeiden-Arten. 129. Beitrag zur Kenntnis der Scarabaeoidea (Coleoptera). - Balthasar, Vladimir (Contributions to Entomology = Beiträge zur Entomologie, 1968)
Four new species of Scarabaeidae from the ethiophian region are described. Parascarabaeus Balthasar was found to be a synonym of Sceliages Westwood.Nomenclatural Actstransvaalensis Balthasar, 1968 (Catharsius (Metacatharsius)), spec. n.lohsei Balthasar, 1968 (Chironitis), spec. n.Parascarabaeus Balthasar, 1961 (Scarabaeidae), syn. n. of Sceliages Westwood,natalensis Balthasar, 1968 (Sisyphus (Sisyphus)), spec. n.asmarensis Balthasar, 1968 (Tiniocellus), spec. n.